An empirical study on technological innovation and corporate competitiveness of listed coal-to-liquids companies in China - Song, Meihui; Wang, Zhenqin; Wang, Weicai (Frontiers in Environmental Science, 2022)
Technological innovation in the CTL industry is an important direction for China’s future development. Taking the China’s listed CTL companies as samples, this study makes an empirical test on the relationship between technological innovation capabilities and corporate competitiveness of CTL companies, and explores the regulating effect of enterprise scales on the relationship between technological innovation capabilities and corporate competitiveness, as well as the mediating effect of product differentiation on this relationship. It is found that the investment capacity of CTL enterprises for technological innovation has a significant driving effect on their competitiveness (with the correlation coefficient of 0.017), the output capacity of technological innovation has no remarkable effect on the promotion of the enterprises’ competitiveness(with the correlation coefficient of 0.0298), enterprise scales have a positive regulating effect on the relationship between technological innovation input and output capabilities and corporate competitiveness (with the coefficient of the interaction term of 0.3870 and 0.0002 respectively) , and product differentiation plays a mediating effect on this relationship (with the coefficient of the interaction term of 0.147 and 0.096 respectively). From the results, it can be said that increasing R&D expenses of enterprises, encourage the cultivation and introduction of high-end R&D talents as well as strengthen technological innovation and enhance product differentiation can help to improve CTL enterprises’ competitiveness. The conclusions of this study can provide theoretical bases for CTL enterprises to hike and improve their competitiveness in terms of technological innovation.